Polymorphisms of nucleotide excision repair genes associated with colorectal cancer risk: Meta-analysis and trial sequential analysis - Yi, Chuncheng; Li, Tiandong; Shen, Yajing; Wang, Peng; Dai, Liping; Shi, Jianxiang; Wang, Keyan; Sun, Changqing; Ye, Hua (Frontiers in Genetics, 2022)
Background Reduced DNA repair capacity in nucleotide excision repair (NER) pathways owing to genetic variant may influence cancer susceptibility. According to published studies, variants of NER genes associations with colorectal cancer (CRC) risk were inconclusive. Thus, this meta-analysis aimed to explore the possible association. A test sequence analysis (TSA) analysis was conducted to control the risk of false positive or false negative. Methods PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Network (CNKI), Wanfang Database and Scientific and Technical Journal Database (VIP) were searched to identify relative studies until April 2022. The association was assessed by odds ratio (OR) in Allele, homozygous, heterozygous, dominant, recessive, and over-dominant models. In addition, Begg's and Egger's tests, sensitivity analysis, subgroup analysis and TSA analysis were performed. Results A total of 29 studies were eventually included in the meta-analysis, including 12,153 CRC patients and 14,168 controls. It showed that excision and repair cross complementary group 1 (ERCC1) rs11615 CC genotype decreased the risk of CRC, compared with TT genotype (CC vs. TT: OR = 0.816, 95%CI = 0.673-0.990, P = 0.039). For ERCC1 rs3212986, the significant impact was detected on increased the risk of CRC in the allele (OR = 1.267, 95%CI = 1.027-1.562, P = 0.027), homozygous (OR=1.805, 95%CI = 1.276-2.553, P = 0.001), dominant (OR = 1.214, 95%CI = 1.012-1.455, P = 0.037) and recessive (OR = 1.714, 95%CI = 1.225-2.399, P = 0.002) models, especially in the Asian population. The results revealed the association of ERCC2 rs1799793 A allele with a higher risk of CRC (A vs. G: OR = 1.163, 95%CI = 1.021-1.325, P = 0.023). It also showed that ERCC5 rs17655 increased CRC risk in the allele, homozygous, heterozygous, dominant and over-dominant (OR = 0.828, 95%CI = 0.762-0.900, P < 0.001) models, especially among Asians. Conclusion This meta-analysis based on current evidence suggests that the significant association was observed between ERCC1 rs11615, ERCC1 rs3212986, ERCC2 rs1799793, and ERCC5 rs17655 and CRC susceptibility. However, given the limited sample size and the influence of genetic background, studies of a larger scale and well-designed are required to confirm the results.